Physiology at a glance - Ward, Jeremy P. T. (At a glance series (Oxford, England), 2013)
This revised and updated edition of Physiology at a Glance features clear and concise illustrations, memorable data tables, and easy-to-read text, to provide a thorough introduction to physiology that integrates seamlessly with the medical school curriculum. Physiology at a Glance breaks the topic down into its core components, dealing with structures of the body from cellular level to composite systems. Each chapter focuses on an element of the body and explores vital concepts to aid students at all levels of their training. Physiology at a Glance:<br.